Probiotics and Prebiotics as A Preventive and Therapeutic Tool : Unveiling Their Role in Disease Prevention, Treatment, And Holistic Health Management - Navreet Kaur Bains; Dr. Charan Singh (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This clinical research examines the currently recognised health advantages of probiotics and prebiotics. When consumed, probiotic supplements and foods modify the flora of the intestinal tract by introducing live bacteria into the system. Research has revealed that probiotics are only marginally beneficial in treating acute infectious gastroenteritis in healthy children and preventing antibiotic-associated diarrhoea in healthy children, both of which can be caused by antibiotics. However, further research is needed before concluding that probiotics can prevent necrotizing enterocolitis in really low birth weight newborns. In RCTs involving the use of probiotics to treat and prevent childhood atopy, preliminary results are positive, but more research is needed to validate their efficacy in treating and preventing gastrointestinal conditions in children. Cancer and Crohn’s disease have not been shown to benefit from probiotics, nor have they been shown to prevent cancer in humans. Using probiotics in infants and children who are immune compromised, chronically unwell, or critically ill with indwelling medical devices raises additional safety issues. Non-digestible food ingredients, such as prebiotics, boost the growth and/or activity of indigenous probiotic bacteria in a manner that is beneficial to the human body. Prebiotics are found in human milk in large concentrations. Children may benefit from long-term prebiotic use for atopic eczema and common infections in healthy newborns, however RCTs on the topic are scarce in children. Validating clinical research studies with sound design are required.